Pencegahan Bahaya Anti Narkoba pada Generasi Muda : Growth with Healthy Mindset Without Drugs - Suheriah Mulia Devi; Angga Dwi Pramudika; Angelica Eugini Virgie (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
The problem of drug abuse among adolescents poses a serious threat to the sustainability of human resource quality, especially in strategic areas such as Nenang Village, Penajam Paser Utara Regency. This community service activity aims to increase awareness and mental resilience among 8th-grade students of SMPN 10 Penajam Paser Utara through a socialization program entitled